The Certainty of Change: Flood, Drought, and the Genre of Environmental Prophecy in California's Central Valley, 1987-2015 - Grant, Daniel A (My University, 2015)
Disaster studies, a field that gained prominence in the 1970s in response to growing research on environmental hazards, has now become a robust nexus for geographers, anthropologists, historians, and cultural critics. In 1942, the physical geographer Gilbert White published a groundbreaking work that famously declared that “floods are ‘acts of God,’ but flood losses are largely acts of man.” Such a clear distinction between a hazard and the human experience of that hazard as a “disaster” prompted further inquiry into understanding what came to be called the “human ecological approach” in disaster studies. Such an approach focused less on the natural hazard (flood, drought, etc.) than on the processes both structural and particular that made people vulnerable. This focus is perhaps best exemplified by the proliferation of models that attempted to “explain” natural disasters in their complex social and environmental contexts--a laudable if daunting prospect to which many have made valuable contributions. Phrases such as “progression of vulnerability,” “causal essence of calamity,” and “chain of human choices and natural occurrences” annotate these models. It is, to be sure, an impressive feat to distill and separate such complex phenomena into discrete schematics that can seemingly be applied to any natural disaster. The famous “pressure and release” model of vulnerability, for example, resembles a nutcracker, where each box is connected to the next one by an arrow to connote a sequential progression from “root causes” to “dynamic pressures” to “unsafe conditions.” On the other side of the model, with arrows pointing the opposite direction, is the hazard itself. Combine these two sides and one has the makings for a disaster. But while these diagrams are simple, neat, and offer the comfort of explanations that can be translated from one disaster to the next, they also embody the very problems that I wish to address.
Includes table of contents, bibliography
Keywords: Drought; Flood; Natural disaster; Prophecy; California